2012
DOI: 10.1159/000336245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sebum on Drug Transport across the Human Stratum Corneum in vivo

Abstract: The objective of this study was to investigate the effect of sebum on drug transport across the human stratum corneum (SC) in vivo for two model compounds, 4-cyanophenol (CP) and cimetidine (CM), of different lipophilicity and molecular size by utilizing noninvasive tape-stripping techniques, in conjunction with an unsteady-state diffusion model for data analysis. The results demonstrated that the SC permeability of the relatively hydrophilic CM on the forehead may be as much as four times the permeability on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…These data are suggestive that the combination of artificial sebum and aqueous vehicles containing ZnPT increases the permeability of the skin under these experimental conditions. Similar results were obtained by Tsai et al [50] who measured a 2- to 3-fold increase in the transverse diffusion coefficients for 4-cyanophenol and cimetidine applied to sebum-supplemented skin compared to untreated skin in vivo. In that study, the authors noted that sebum treatment increased the SC permeability and altered barrier function by disordering structures of the intercellular lipid bilayers.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…These data are suggestive that the combination of artificial sebum and aqueous vehicles containing ZnPT increases the permeability of the skin under these experimental conditions. Similar results were obtained by Tsai et al [50] who measured a 2- to 3-fold increase in the transverse diffusion coefficients for 4-cyanophenol and cimetidine applied to sebum-supplemented skin compared to untreated skin in vivo. In that study, the authors noted that sebum treatment increased the SC permeability and altered barrier function by disordering structures of the intercellular lipid bilayers.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…These findings suggest that not only the anti-inflammatory agent (MF) itself but also the formulation will play an important role in the treatment of skin disorders like atopic dermatitis. It was demonstrated that the amount of sebum affects the permeability of skin to molecules and the presence of sebum on the forehead or forearm increased the diffusion of both hydrophilic and lipophylic molecules through the human skin (Tsai et al, 2012). The increase of the amount of lipids in the SC can, thus, explain the formulation effect on the enhancement of MF permeation across the human epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Human sebum extract used in this study consisted of approximately 36.4% free fatty acids, 15.5% triglycerides, 22% wax esters, 20.6% squalene, and 5.5% cholesterol/cholesterol esters, as previously reported [10]. Following sebum applications, redness began to appear on the dorsal skin of hairless mice on day 1 (i.e., S1D, 24 h after the 1st sebum application), and then minor scales appeared on day 2 (S2D, i.e., 24 h after the 2nd sebum application, data not shown).…”
Section: Application Of Human Sebum Induced Scales Erythema Perturbmentioning
confidence: 98%
“…Six healthy male volunteers (>20 y/o) were included in the study. The skin surface lipids were obtained by pouring 400 mL of 95% ethanol through the scalp [10][11][12]. The solution was then filtered through a quantitative filter paper to remove particles, followed by rotary evaporation to remove solvent.…”
Section: Collection Of Human Sebum Extractmentioning
confidence: 99%
See 1 more Smart Citation